C4 photosynthesis and the economic spectra of leaf and root traits independently influence growth rates in grasses. (1st June 2020) - Simpson, Kimberley J.; Bennett, Christopher; Atkinson, Rebecca R. L.; Mockford, Emily J.; McKenzie, Scott; Freckleton, Robert P.; Thompson, Ken; Rees, Mark; Osborne, Colin P.
Abstract: Photosynthetic pathway is an important cause of growth rate variation between species such that the enhanced carbon uptake of C4 species leads to faster growth than their C3 counterparts. Leaf traits that promote rapid resource acquisition may further enhance the growth capacity of C4 species. However, how root economic traits interact with leaf traits, and the different growth strategies adopted by plants with C3 and C4 photosynthetic pathways is unclear. Plant economic traits could interact with, or act independently of, photosynthetic pathway in influencing growth rate, or C3 and C4 species could segregate out along a common growth rate–trait relationship. We measured leaf and root traits on 100+ grass species grown from seeds in a controlled, common environment to compare with relative growth rates (RGR) during the initial phase of rapid growth, controlling for phylogeny and allometric effects. Photosynthetic pathway acts independently to leaf and root functional traits in causing fast growth. Using C4 photosynthesis, plants can achieve faster growth than their C3 counterparts (by an average 0.04 g g −1  day −1 ) for a given suite of functional trait values, with lower investments of leaf and root nitrogen. Leaf and root traits had an additive effect on RGR, with plants achieving fast growth by possessing resource‐acquisitive leaf traits (high specific leaf area and low leaf dry matter content) or root traits (high specific root length and area, and low root diameter), but having both leads to an even faster growth rate (by up to 0.06 g g −1  day −1 ). C4 photosynthesis can provide a greater relative increase in RGR for plants with a 'slow' ecological strategy than in those with fast growth. However, above‐ground and below‐ground strategies are not coordinated so that species can have any combination of 'slow' or 'fast' leaf and root traits. Synthesis . C4 photosynthesis increases growth rate for a given combination of economic traits, and significantly alters plant nitrogen economy in the leaves and roots. However, leaf and root economic traits act independently to further enhance growth. The fast growth of C4 grasses promotes a competitive advantage under hot, sunny conditions. Abstract : Photosynthetic pathway acts independently to leaf and root functional traits in causing fast growth in a sample of 100+ grass species. Using C4 photosynthesis, plants can achieve faster growth than their C3 counterparts for a given suite of functional trait values, with lower investments of leaf and root nitrogen.